PRICING OF WATER RESOURCES USED IN THE PRODUCTION OF DATES IN SAUDI ARABIA - S. H. Al Kahtani; A. M. Ghanem (Journal of Animal and Plant Sciences, 2013)
The aim of this study is to determine the pricing of water resources used in the production of dates, based on the estimated production function and the derivative functions of marginal product and the marginal water resources return. Then calculating the value of marginal water resources return, which are equal to marginal costs (the unit price of resource) at the point of economic efficiency. The most important findings include the following: according to the local market price, the average unit price of water used in the production of dates ranged between the minimum of 0.51 SR / m 3 in the Jawf region up to maximum of 0.75 SR / m 3 in the eastern region, with an average estimated at 0.63 SR / m3 . While at the export price (social price for dates), the unit price of water used in the production of dates ranged between the minimum of 0.30 SR / m 3 in the Jawf region up to maximum of 0.40 SR / m3 in the eastern region, with an average estimated 0.34 Real / m3 . At increasing the unit price of water used in the production of dates by 50%, it is expected to decrease the amount of water used in the production of dates in Riyadh region from 27.66 thousand m3 / ha to 12.29 thousand m 3 / ha. In the eastern region is expected to decrease the amount of water used in the production of dates from29.28 thousand m 3 / ha to 13.42 thousand m3 / ha. Finally, it is expected to decrease the amount of water used in the production of dates in Jawf region of 32.86 thousand m 3 / ha to 15.72 thousand m3 / ha. The study recommends the need to include water in the context of economic value in order to rationalize water consumption, preserved water for future generations, and achieving sustainable agricultural development.
Keywords: water pricing; revenue and marginal cost of water; dates